Prevention, management and control of peste des petits ruminants in Uganda - International Livestock Research Institute (International Livestock Research Institute, 2021)
Peste des petits (PPR) which is also known as ovine rinderpest, is a prevalent viral disease among small ruminants, mainly goats, sheep and wild animals. This film highlights the work of various stakeholders working with the Boosting Uganda's Investment in Livestock Development (BUILD) Uganda project in the prevention, management and control of pest des petits ruminants (PPR) in the country.